1995
DOI: 10.1172/jci117680
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 gene induction in the myocardium after ischemia and reperfusion in vivo.

Abstract: Neutrophil adhesion and direct cytotoxicity for cardiac myo-cytes require chemotactic stimulation and are dependent upon CD18-ICAM-1 binding. To characterize the potential role of IL-8 in this interaction, canine IL-8 cDNA was cloned and the mature recombinant protein expressed in Escherichia coli BL21 cells. Recombinant canine IL-8 markedly increased adhesion of neutrophils to isolated canine cardiac myocytes. This adhesion resulted in direct cytotoxicity for cardiac myocytes. Both processes were specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
120
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(130 citation statements)
references
References 32 publications
5
120
0
5
Order By: Relevance
“…They were even detected in the circulation of these animals, be it only during the first day posttransplantation. This short episode of elevated circulating levels does not exclude that both proteins remain produced and locally released at later times but indicates that the immediate posttransplant period favors their release, possibly as an effect of the hypoxic and/or inflammatory environment, which is known to induce IL-8 and VEGF production (26,27). When comparing data from independent experiments, we observed a high variation in the mRNA expression level of both proteins.…”
Section: Discussionmentioning
confidence: 71%
“…They were even detected in the circulation of these animals, be it only during the first day posttransplantation. This short episode of elevated circulating levels does not exclude that both proteins remain produced and locally released at later times but indicates that the immediate posttransplant period favors their release, possibly as an effect of the hypoxic and/or inflammatory environment, which is known to induce IL-8 and VEGF production (26,27). When comparing data from independent experiments, we observed a high variation in the mRNA expression level of both proteins.…”
Section: Discussionmentioning
confidence: 71%
“…Multiple factors initiate LV inflammation, including complement activation (38), reactive oxygen species generation (39), cytokines (40), and chemokines (41,42). Neutrophils contribute to cardiac myocyte damage in LV ischemia by releasing reactive oxygen species, proteases, cytokines, vasoconstricting lipids, and up-regulating adhesion molecules (35).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, it has been shown that neutrophils first penetrate the infarcted myocardium, followed by macrophages, and it has been reported that neutrophils are associated with reperfusion injury, in concert with the induction of intracellular adhesion molecule-1 (ICAM-1), interleukin (IL)-6, or IL-8 (Hawkins et al, 1996;Kukielka et al, 1993Kukielka et al, , 1995aKukielka et al, , 1995bNeumann et al, 1995;Youker et al, 1994). It has also been reported that reperfusion is associated with an increase in the number of macrophages compared with the nonreperfused Mean number of macrophages in the hearts at 1 hour, 3 hours, and 6 hours after reperfusion (R).…”
Section: Discussionmentioning
confidence: 99%